Central giant cell granuloma: a case report. (22nd July 2013) - Mohan, Ravi Prakash Sasankoti; Verma, Sankalp; Agarwal, Neha; Singh, Udita
Abstract : Central giant cell granuloma (CGCG) is a relatively uncommon benign bony lesion of a variably aggressive nature. Thought to represent a reparative response to intrabony haemorrhage and inflammation, CGCG was once regarded as a reactive lesion. It is actually an asymptomatic lesion which becomes evident during routine radiographic examination or as a result of painless but visible expansion of the affected jaw. This paper presents the case of a 4-year-old boy with CGCG in the right mandibular region.